POLA PENCEMARAN LOKASI PENANGKAPAN DAN IKAN HASIL TANGKAPAN AKIBAT BERKEMBANGNYA AKTIVITAS EKONOMI DI SEKITAR DANAU MANINJAU - Mustaruddin Mustaruddin; Eko Sri Wiyono; Mohammad Khotib; Asnil Asnil; Samsul Bahri (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Maninjau Lake is the territorial waters of which contribute greatly to fish production in Agam, West Sumatra. But a lot of waste of economic activities discharged into the lake. This study aims to analyze the characteristics of fishing, contamination status of fishing ground and fish caught, to analyze the contamination pattern of fishing ground and fish caught as effect of economic activity waste. The methods used are descriptive method, physic-chemical analysis, correlation method, and multiple regression method. The results showed the fishing in Lake Maninjau, generally using langli net, lift net, hook and lines, and cast net. While the main fish caught are nile tilapia, bada fish, rinuak fish, carp, and limbek fish. Fishing ground in Maninjau Lake contaminated by ammonia, garbage, Cd and Hg metals, while the fish caught, there was found to have gills dirty. Significantly, fishing ground disturbed by the waste of hydropower (X1), lake tourism (X2), settlements (X4), and KJA fisheries (X5). The contamination pattern of fishing ground formulated by Y1=0,220X1+0,085X2+0,227X4+0,204X5-4,540. Fish production disturbed significantly by the waste from hotel and restaurants (X3), seattlements (X4), and KJA fisheries (X5). The contamination pattern of fish caught, represented by a decrease in fish production (Y2) formulated by Y2 =1,195X3+2,152X4+5,140X5-41,664.